An Analysis of Persuasive Communication with Ethnographic Communication Approach at Junior High Schools in West Bandung - Encep Rustandi; Syihabuddin; Yayan Nuryanto (Jurnal Komunikasi Pendidikan, 2025)
Improving student discipline is one of the main challenges in the education system. This study explores the application of persuasive communication patterns in improving the discipline of high school students in West Bandung with the SPEAKING approach from Dell Hymes. This approach identifies relevant communication components, including settings, participants, goals, and norms, to produce more effective interactions between teachers and students. This study uses qualitative methods with in-depth interviews and participant observations to analyze the application of persuasive communication strategies in the school environment. The results of the study indicate that the Persuasive communication pattern is able to build more harmonious relationships, foster intrinsic motivation, and increase student compliance with school regulations.